Culture and social change : transforming society through the power of ideas - Wagoner, Brady, 1980-; Jensen, Eric, 1981-; Oldmeadow, Julian A. (Emerald Publishing Limited : Information Age Pub., 2012)
This book brings together social sciencists to create an interdisciplinary dialogue on the topic of social change as a cultural process. Culture is as much about novelty as it is about tradition, as much about change as it is about stability. This dynamic tension is analyzed in collective protests, intergroup dynamics, language, mass media, science, community participation, art, and social transitions to capitalism, among others contexts. These diverse cases illustrate a number of key factors that can propel, slow-down and retract social change. An emancipatory and integrative social science is developed in this book, which offers a new explanatory model of human behavior and thought under conditions of institutional and societal change.
Keywords: Culture -- Psychological aspects.; Social change.; Social Science -- Anthropology -- Cultural & Social.; Cultural studies.; Social and cultural anthropology.; elektronické knihy; electronic books